Being with a Puppet: Literacy through Experiencing Puppetry and Drama with Young Children - Olivia Karaolis (MDPI AG, 2023)
Puppets have a long association with early childhood education and have played a much-loved role in children's learning and development. This paper tells the research story that investigated how the magical creature of a puppet facilitated connection, play, communication, and engagement with children who experience disability. We discovered how puppets can be combined with drama approaches and utilized in group activities for enabling literacy development by early childhood educators. In being with a puppet, adults found new 'ways' of supporting all children's interest, meaning making, and contribution to group learning experiences. Puppets were found to invite children into conversations, to encourage their expression and creativity, in a way that was uniquely their own. Educators found that being with a puppet supported their relationship with the children to one that was more playful and positive as it altered their perception of the children and their ability to recognize their non-verbal communication.